Vibrational Circular Dichroism Unravels Supramolecular Chirality and Hydration Polymorphism of Nucleoside Crystals. Issue 63 (12th September 2022) - Krupová, Monika; Leszczenko, Patrycja; Sierka, Ewa; Emma Hamplová, Sára; Pelc, Radek; Andrushchenko, Valery
Abstract: Vibrational circular dichroism (VCD) spectroscopy has been widely used to study (bio)molecules in solution. However, its solid‐state applications have been restricted due to experimental limitations and artifacts. Having overcome some of them, the first VCD study of nucleoside crystals is now presented. A two‐orders‐of‐magnitude enhancement of VCD signal was observed due to high molecular order in the crystals and resulting supramolecular chirality. This allowed to obtain high‐quality VCD spectra within minutes using minute amounts of samples. The VCD technique is extremely sensitive in detecting changes in a crystal order and is able to distinguish different hydration states of crystals. This elevates it to a new level, as a fast and efficient tool to study chiral crystalline samples. This study demonstrates that VCD is capable of near‐instantaneous detection of hydration polymorphs and crystal degradation, which is of substantial interest in pharmaceutical industry (quality and stability control). Abstract : Supramolecular VCD of nucleoside crystal solvomorphs : Vibrational circular dichroism (VCD) spectra of guanosine microcrystals exhibit sign inversion upon reversible crystal hydration/dehydration. Such spectral changes occur due to alteration of molecular arrangement in the crystal. Supramolecular chirality of the crystals brings about two‐orders‐of‐magnitude enhancement of the VCD signal, thus enabling almost instantaneous spectra measurements. This could be utilized in pharmaceutical industry, e. g. for quality and stability control.